Adherence to lifestyle recommendations of the World Cancer Research Fund/american Institute for Cancer Research of breast cancer survivors on adjuvant hormone therapy and associated factors - Jardim, Luisa Comerlato; Flores, Priscila Trindade; dos Santos Araújo, Maria do Carmo; Chieza, Juarez; Marques, Clandio; Antoniazzi, Raquel Pippi; de Moraes, Cristina Machado Bragança (Disciplinarum Scientia | Saúde, 2021)
About 30% to 40% of cancers can be prevented through healthy diet, adequate body weight and regular physical activity. The adherence to lifestyle recommendations of the World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) has been associated with lower risk of death in cancer survivors. The objective of this study was to evaluate adherence to the new recommendations of the WCRF/AICR by Brazilian women in adjuvant hormone therapy for breast cancer and its associated factors. This cross-sectional study was carried out from January to August 2017, in Santa Maria, RS. Regarding the recommendations of the WCRF/AICR the average adherence score was 4.4 points out of a total of 8 points. Higher adherence is associated with higher schooling. In individual recommendations, physical activity showed the lowest adherence whereas alcohol consumption showed the highest adherence. The data suggest that Brazilian breast cancer survivors, especially those with lower levels of education, could benefit from dietary counseling and physical activity.